Simple, Easy-use and Low-cost Software for Design of Single and Cascaded Microring Resonators Using Semi-numerical Method - Budi Mulyanti; Lilik Hasanah; Tommi Hariyadi; Arjuni B Pantjawati; Heru Yuwono; P. Susthita Menon; Sahbudin Shaari (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2015)
Development of a simple, easy and low-cost software for designing of waveguide-coupled single and cascaded microring resonator (MRRs) using semi-numerical calculation based on transfer matrix method (TMM), is presented in this paper. The software uses a device model which is embedded on the high index contrast (HIC) structure of silicon-on-insulator (SOI) with monomodal cavity for TE-mode polarizations, operating around 1550 nm optical wavelength. The main aim of the software is to estimate the microring resonator performance parameters, such as free spectral range (FSR) and quality factor (Q-factor). The software is very simple and easy to use. With a standard laptop computer, it only takes few seconds to obtain transmission response, FSR and Q-factor of single MRR for varied waveguides separation distance and ring radius. The results were then verified using simulation method based on finite integration technique using 3D electromagnetic simulator, which need a high memory and processor of computer and take days to execute the simulation. We found only small discrepancy, which in averages are about 4.25% and 10.80% for FSR and Q-factor, respectively. In general, the results obtained from this software are closer to 3D electromagnetic simulation results.